"Uso pa ba ang OPM?”: A Semantic Analysis of Original Pilipino Music (OPM) Songs Preferred by Filipino Youth - Lano, Erik Martin C. (Animo Repository, 2023)
Original Pilipino Music (OPM) has been significant to Filipino culture and society for years, reaching its peak at the height of the COVID-19 global pandemic. Its influence continues to cross borders globally and locally, echoing individual experiences, emotions, ideas, and alike. The popular music composed by Filipinos has been a powerful catalyst for organizing, unifying, and mobilizing individuals around a shared goal. It serves as a means of expression and communication, allowing individuals to expand their feelings on timely subjects and bring them to the surface. Hence, this study aims to pinpoint Filipino youth's preference for OPM through an online survey and Geoffrey Leech's Semantic Theory. The study identified the common types of meaning based on the theory for the top-selected five songs and analyzed whether there are recurring types of meaning among these OPM songs. The Results show that Geoffrey Leech's seven types of meaning were evident in the lyrics of the OPM songs chosen by the respondents in the study. Some types of meaning appear more apparent than others among the top-selected songs, which parallel the popularity of the Pop and Indie genre of OPM among the Filipino youth.